PENERAPAN NEO VERNAKULAR PADA KANTOR DINAS KEBUDAYAAN, PARIWISATA, KEPEMUDAAN DAN OLAHRAGA KABUPATEN BARITO UTARA - Muhammad Pujiadi Anggara Pramana Putra Mandalika; Nursyarif Agusniansyah; Gusti Novi Sarbini (ULM Press, 2024)
The tourism sector has an important role in building the economy of a region. After the pandemic ended, tourism in Indonesia began to increase due to the acceleration of government performance in an effort to increase development and promotion in the tourism sector. The North Barito Regency Disbudparpora Office is a government agency facility that handles affairs in the culture, tourism, youth and sports sectors in the North Barito district. The Disbudparpora of North Barito Regency has the responsibility of accelerating performance in the form of development and promotion in the culture, tourism, youth and sports sectors to the community. The use of neo vernacular architecture concept is expected to be able to get a functional design solution as a workplace while accommodating development and promotion activities with modern building visuals but still applying elements of tradition and local architecture of the North Barito district.